Immunocytochemical staining of cervical smears – A comparative study with routine cytology for confirmation of precancerous and cancerous lesions of cervix - Varsha Pandey; Manju Raj Purohit; P. L. Dhand (International Journal of Medical Research and Review, 2016)
Introduction: Carcinoma cervix is one of the leading causes of morbidity and mortality. The most effective method of screening is based on Pap smear study. However, Pap smear has relatively low sensitivity and irreducible false negative & false positive rates. In countries like India, it is not always feasible to follow the patient for confirmation by histology. In the present study, we have tried to fill this gap by staining the cervical smears with, epithelial cell markers including CK17 and CEA expressed by dysplastic squamous cells.Materials & Methods: 50 cervical smears reported as precancerous or cancerous were stained with anti CK17 and anti CEA. The patients were followed for histopathology.Results: Out of 20 cases of ASCUS, three were positive both for anti-CK17 and anti-CEA and six were positive for anti-CK17 only. Out of 18 cases of LSIL, nine were positive for both anti-CK17 and anti-CEA and fifteen were positive for anti-CK17 only. Out of eight cases of HSIL, three were positive for both anti-CK17 and anti-CEA and six were positive for anti-CK17 only. Out of 4 cases of SCC, three were positive for both anti-CK17 and anti-CEA and all four were positive for anti-CK17.Conclusion: Positive result in staining was higher in high grade lesions. CK 17 was found to be better marker than CEA. CK17 and CEA can be used as adjunct to Pap smear screening but its high cost may restrict its use in routine.